Risks and Efficiency in the Islamic Banking Systems: The Case of Selected Islamic Banks in MENA Region - Said, Ali (International Journal of Economics and Financial Issues, 2012)
The present paper examined the correlation between risks and efficiency within Islamic banks in the MENA area. This paper used three stages of analyses. The first stage consisted of measuring the efficiency of those banks by employing the nonparametric technique, Data Envelopment Analysis (DEA) while the second stage involved analyzing risks by measure credit, operational, and liquidity risks using financial ratios. The third stage would be employing Pearson Correlation Coefficients to examine the correlation between credit, operational, liquidity risks to efficiency for the period of 2006 to 2009. The study results have revealed credit risk has negative relationship to efficiency, while operational risk has found to be negatively correlated to efficiency too. The liquidity risk showed insignificant correlation to efficiency in Islamic banks in MENA area. Keywords: Efficiency; Liquidity Risk; Credit Risk; Operational Risk; Islamic Banks; MENA banking; Data Envelopment Analysis. JEL Classifications: G01; G21; G24; G29